The influence of emotional intelligence, job stress, and job satisfaction on head teachers job performance in Palestine - Abuayyash, Hadeel Adel Hasan
Education sector plays a vital role in the social development and economic growth of any society in the world. Palestinian government has taken many steps to improve the quality of education. However, many expressed dissatisfactions with the performance of head teachers affected by lack of school development. The decline in head teachers' performance in Palestinian primary schools was reported to be caused by low salary and 10 morale. Those issues had led to a large number of applications for early retirement by head teachers. Many past studies indicated the significant influence of several behavioural factors that might promote head teachers' performance in primary schools, including emotional intelligence, job stress, and job satisfaction. However, none of the studies had examined the combined factor-performance relationships within a single model. Hence, the study was purported to investigate the influence of emotional intelligence, job stress, and job satisfaction on the job performance of head teachers at Palestinian primary schools. The study had adopted a quantitative method that made use of a structured questionnaire consisting of 14 job performance items, 10 emotional intelligence items, 10 job stress items, and 10 job satisfaction items that were adapted from previous research. Each construct was measured using a seven-point rating scale. The questionnaire was pre-tested so that it achieved content validity and face validity. Content validity was verified to ensure that the questionnaire contained an exhaustive list of items for measuring the concepts of interest based on suggestions sought from five specialist academics. To obtain face validity, the questionnaire was distributed to 10 typical participants to ascertain that its items represent the right measures of the concepts being studied. A pilot study ensued where 100 head teachers had completed the questionnaire to provide data that were used to compute the reliability of the measurement scales. The instrument was then distributed to randomly selected respondents comprising of 205 primary school head teachers from a population of 420 at three directorates in Hebron using cluster sampling method. To validate the model, data were subjected to frequency analysis, correlation analysis and multiple regression analysis on Statistical Package for Social Science (SPSS) version 25.0. The research findings showed that emotional intelligence and job satisfaction had a significant positive relationship with head teacher performance. On the other hand, job stress had an inverse proportional relationship with performance. The head teachers also perceived that they could appropriately control their emotions to cope with job stress, resulting in job satisfaction that ultimately lead to better performance. Emotional intelligence was also a factor in predicting head teacher performance. The research had validated a new conceptual model of factors influencing head teacher performance. The job performance of head teachers could be enhanced if emotions and stress are managed effectively, resulting in job satisfaction. The result of the study had implications on the Palestinian Ministry of Education with respect to the use of valid measures to evaluate the performance of primary school head teachers and provision of holistic knowledge on effective school administration.